Development of AKSI Books Based on the Discovery Learning Model to Improve the Creativity of Grade III Elementary School Students - Mutiara Rahma; Deni Setiawan (Journal of Practice Learning and Educational Development, 2026)
This study aims to develop the AKSI Book (Ayo Kreasi Seni Kolase Interaktif) based on the Discovery Learning model to enhance collage art creativity of third-grade elementary school students and to examine its feasibility, practicality, and effectiveness in improving students’ creativity. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 30 third-grade students of SDN Tambakaji 01 Semarang. Data were collected through interviews, questionnaires, and creativity tests, while data analysis was conducted using descriptive quantitative techniques and statistical analysis. The validation results indicated that the AKSI Book was categorized as highly feasible by media experts with a score of 96.25% and by material experts with a score of 92%. The teacher response showed a practicality level of 85%, which was categorized as very feasible. The effectiveness test revealed a significant improvement in students’ creativity after the implementation of the AKSI Book. This was indicated by the paired-sample t-test significance value of 0.000 (< 0.05), an increase in the mean creativity score from 68.93 in the pretest to 85.67 in the posttest, and an N-Gain value of 0.54 in the moderate category. Therefore, the Discovery Learning–based AKSI Book is feasible, practical, and effective as a supplementary teaching material for collage art learning to improve elementary school students’ creativity.